On Islamic Accounting - Muhammad Akram Khan (International Institute of Islamic Thought, 1994)
Islamic accounthg is an emerging field of study. With the establishment of several Islamic banks, interest in this area has increased. The present booklet is a master’s thesis, submitted to the Intemational University of Japan, consisting of four chapters and five appendices. Chapter one reviews western accounting and its evolution. Its main argument is that western accounting developed in response to the needs of evolving capitalism. Due to social assumptions of the primacy of self-interest and the profit motive, accounting serves the needs of business and not those of society. Society makes only an indirect use of a business entity’s accounting statements. In chapter two, the author introduces the basic concept of Islamic accounting. According to him, Islamic accounting is more responsive to a society’s needs. The accounting statements prepared in an Islamic framework provide essential information needed by the society. For example, they are useful for calculating zakat. Chapter three deals with the actual accounting of zakat. The author examines the controversy of whether zakat should be treated as a cost or as part of the appropriation account in a mudiirubuh arrangement. He supports the contention that it should be treated as a cost. The last chapter summaries the debate and concludes that western accounting should make use of the Islamic accounting concept’s of responding to the needs of a society rather than a business. The book is a welcome addition to the meager literatw on the subject. The author has examined some primary sources in order to base his argument, although he has also relied on secondary source. But the reader does not find what he expects for, with the exception of one major observation about the scope of accounting in the Islamic and western frameworks, there is little on the differences between the two concepts. For example, he does not compare their assumptions, standards, procedures, and methods. Perhaps these questions were not part of the book‘s scope. However, I think such a discussion would be of interest to many readers ...